Gold vinylidene complexes: intermolecular C(sp3)H insertions and cyclopropanations pathways - Hashmi, A. Stephen K.; Wieteck, Marcel; Braun, Ingo; Rudolph, Matthias; Rominger, Frank (Angewandte Chemie. International edition, 2012)
Highly reactive gold vinylidene species are used for intermolecular C(sp3)H insertions into unactivated alkanes (see scheme). In addition, they can be regarded as synthons for alkylidene carbenes. Initiated by cyclopropanation of the vinylidene species/alkylidene carbenoide, cyclobutene derivatives are formed in a diastereoselective fashion by a ring-enlargement cascade in only one step.
Die Zahl 3 im Titel ist hochgestellt
Version of Record online: 17 September 2012
Gesehen am 06.09.2018